Nevus Comedonicus: A Case Series. Issue 2 (29th December 2014) - Ferrari, Bruno; Taliercio, Vanina; Restrepo, Paola; Luna, Paula; Abad, María Eugenia; Larralde, Margarita
Abstract: Twelve previously unreported cases of nevus comedonicus are presented. Characteristic closely grouped dilated follicular openings with horny plugs that mimic comedones led to the diagnosis. One patient had nevus comedonicus syndrome and there were cases with atypical locations and unusual complications of this condition. We also highlight clinical associations and therapeutic options.